Efficacy and Safety of Qili Qiangxin Capsule on Dilated Cardiomyopathy: A Systematic Review and Meta-Analysis of 35 Randomized Controlled Trials - Wei, Jingjing; Li, Bin; Wang, Xinlu; Li, Xingyuan; Hu, Yucai; Qiao, Lijie; Zhou, Cheng; Yu, Peng; Sang, Tianqing; Zhu, Mingjun; Wang, Yongxia (Frontiers in Pharmacology, 2022)
Objective: Qili Qiangxin Capsule (QQC), a Chinese patent medicine, is clinically effective in treating dilated cardiomyopathy (DCM). However, the meta-analysis of QCC combined with conventional western medicine (CWM) on DCM remains unexplored. This study aimed to systematically evaluate the efficacy and safety of QCC in the treatment of DCM. Methods: Searched the studies of the combination of QQC and CWM in the treatment of DCM, from databases like PubMed, Cochrane Library, Web of Science, Wan Fang Databases, Chinese Biomedical Literature Database, China Science and Technology Journal Database, China National Knowledge Infrastructure, prior to 15 January 2022. Two reviewers respectively regulated research selection, data extraction, and risk of bias assessment. Review Manager Software 5.4 was used for meta-analysis. Furthermore, GRADE pro3.6.1 software was selected to grade the current evidence in our findings. This meta-analysis has been registered in PROSPERO (CRD42022297906). Results: There were 35 studies pertaining to 3,334 patients included. The meta-analysis showed compared with CWM alone, the combination therapy had significant advantages in improving the clinical efficiency rate (RR = 1.24, 95% CI: 1.19 to 1.29, p < 0.00001), 6 min walking distance (6MWD) (MD = 41.93, 95%CI: 39.82 to 44.04, p < 0.00001), superior in ameliorating the left ventricular ejection fraction (LVEF) (MD = 5.73, 95%CI: 4.70 to 6.77, p < 0.00001), left ventricular end-diastolic dimension (LVEDD) (MD = −4.09, 95%CI: −4.91 to −3.27), p < 0.00001), left ventricular end-systolic diameter (LVESD) (MD = −4.73, 95%CI: −5.63 to −3.84), p < 0.00001) and BNP (MD = −101.09, 95%CI: -132.99 to −69.18), p < 0.00001), and also superior in reducing hypersensitive-C-Reactive Protein (hs-CRP) (MD = −3.78, 95%CI: −4.35 to −3.21), p < 0.00001), Interleukin- 6 (IL-6) (MD = −25.92, 95%CI: −31.35 to -20.50), p < 0.00001), tumor necrosis factor-α (TNF-α) (MD = -5.04, 95%CI: −6.13 to −3.95), p < 0.00001), high mobility group protein B1 (HMGB1) (MD = −4.34, 95%CI: −5.22 to −3.46), p < 0.00001), and adverse reactions (ARs) (RR = 0.70, 95%CI: 0.51–0.97), p = 0.03). The GRADE evidence quality rating presented with moderate or low quality of evidence for the available data. Conclusion: Compared with the control group, QQC combined with CWM may be effective in treating DCM. However, the conclusion of this study must be interpreted carefully due to the inferior quality and ambiguity of bias in the included trials. Systematic Review Registration: https://www.crd.york.ac.uk/prospero, identifier [CRD42022297906].